Overconfidence and Herding: How These Biases Affect Generation Z Investments Decision Making - Yuliawati, Tia; Nugraha, Nugraha; Sari, Maya; Waspada, Ikaputera; Purnamasari, Imas; Hendrayati, Heny; Muhamat, Amirul Afif (Image : Jurnal Riset Manajemen, 2024)
The purpose of this study is to understand and analyze the impact of overconfidence bias and herding bias on the investment decisions of Generation Z. This research employs a survey method with a confirmatory approach. Data was collected from a sample of 104 respondents through questionnaires distributed via Google Form. Hypothesis testing was conducted using SEM Analysis with the assistance of SmartPLS 4.0 software. The results of the study indicate that overconfidence bias has a positive and significant influence on the investment decisions of Generation Z, while herding bias does not have a significant influence. Furthermore, this research reveals that the variables of overconfidence bias and herding bias can explain 45.4% of the variation in the investment decisions of Generation Z. However, it is important to acknowledge the limitations of this study, such as the relatively small number of respondents (only 104 respondents) and the absence of comparative analysis with demographic factors of other generational groups (e.g., older generations). This study is expected to provide deeper insights into the investment behavior of Generation Z and serve as a foundation for the development of wiser risk and financial management approaches for this demographic group.